2012
DOI: 10.1038/ncb2445
|View full text |Cite
|
Sign up to set email alerts
|

A 14-3-3γ dimer-based scaffold bridges CtBP1-S/BARS to PI(4)KIIIβ to regulate post-Golgi carrier formation

Abstract: Large pleiomorphic carriers leave the Golgi complex for the plasma membrane by en bloc extrusion of specialized tubular domains, which then undergo fission. Several components of the underlying molecular machinery have been identified, including those involved in the budding/initiation of tubular carrier precursors (for example, the phosphoinositide kinase PI(4)KIIIβ, the GTPase ARF, and FAPP2), and in the fission of these precursors (for example, PKD, CtBP1-S/BARS). However, how these proteins interact to bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 70 publications
5
135
0
Order By: Relevance
“…Our results indicate that 14-3-3c regulates desmosome formation in multiple cell types, as loss of 14-3-3c in HCT116 cells, which are derived from the colon, and in the seminiferous epithelium leads to a decrease in cell-cell adhesion and in desmosome formation. Our results are also consistent with the previously reported role of 14-3-3c in the transport of proteins from the Golgi complex to the cell border (Valente et al, 2012). One reason for the differences in these results and those reported by Steinacker and colleagues (Steinacker et al, 2005) could be that another 14-3-3 family member binds to plakoglobin and stimulates desmosome formation in the 14-3-3c 2/2 mice, and that this compensation is not observed upon shRNA-mediated knockdown in the testis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results indicate that 14-3-3c regulates desmosome formation in multiple cell types, as loss of 14-3-3c in HCT116 cells, which are derived from the colon, and in the seminiferous epithelium leads to a decrease in cell-cell adhesion and in desmosome formation. Our results are also consistent with the previously reported role of 14-3-3c in the transport of proteins from the Golgi complex to the cell border (Valente et al, 2012). One reason for the differences in these results and those reported by Steinacker and colleagues (Steinacker et al, 2005) could be that another 14-3-3 family member binds to plakoglobin and stimulates desmosome formation in the 14-3-3c 2/2 mice, and that this compensation is not observed upon shRNA-mediated knockdown in the testis.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with previous observations that showed that PKCm localizes to the Golgi complex (Hausser et al, 2002;Prestle et al, 1996) and is required for the fission of vesicles carrying cargo to the cell border (Liljedahl et al, 2001). A 14-3-3c dimer is required for carrier formation at the Golgi complex along with PKCm (Valente et al, 2012), suggesting that the loss of 14-3-3c could disrupt desmosome formation owing to defects in plakoglobin transport.…”
Section: Discussionsupporting
confidence: 81%
“…This method allows the determination of protein-protein interactions indicated by an apparent molecular proximity below 10 nm (Eiseler et al, 2012(Eiseler et al, , 2016Gu et al, 2004;Kunkel and Newton, 2009;Oser et al, 2010;Valente et al, 2012;Wille et al, 2014;Wouters et al, 1998;Zeug et al, 2012). The FRET acceptor in a region of interest (ROI) was bleached by an intensive laser line and increase in donor fluorescence, indicating FRET, was measured.…”
Section: Intestinal Permeability Assaymentioning
confidence: 99%
“…Native 14-3-3 exists in monomeric and dimeric states as homo-and heterodimers, respectively, although 14-3-3g is almost entirely dimeric. 57 Glu15 is part of a triad of residues (Leu13, Ala14, and Glu15) necessary for 14-3-3g dimerization, 58,59 and its ability to complex with other proteins is potentially inhibited by substitution at this site.…”
mentioning
confidence: 99%